Medallion „Librarians in time and space”. Tudor Vianu (Confluenţe Bibliologice, 2025)
The article highlights the complex personality of Tudor Vianu, a remarkable Romanian aesthetician, literary critic, philosopher and bibliographer. As director of the Library of the Romanian Academy, Vianu promoted reading as a fundamental means of intellectual and social formation, supporting bibliography as an essential tool of research. He developed and coordinated important bibliographic works and advocated for the professionalization of librarians. Through his theoretical and practical work, Vianu managed to integrate a passion for books with a rigorous vision of the role of the library in society.
Keywords: Vianu Tudor (1898 – 1964); Romanian personalities